2019
DOI: 10.1093/cvr/cvz111
|View full text |Cite
|
Sign up to set email alerts
|

Altered C10 domain in cardiac myosin binding protein-C results in hypertrophic cardiomyopathy

Abstract: Aims A 25-base pair deletion in the cardiac myosin binding protein-C (cMyBP-C) gene (MYBPC3), proposed to skip exon 33, modifies the C10 domain (cMyBP-CΔC10mut) and is associated with hypertrophic cardiomyopathy (HCM) and heart failure, affecting approximately 100 million South Asians. However, the molecular mechanisms underlying the pathogenicity of cMyBP-CΔC10mutin vivo are unknown. We hypothesized that expression of cMyBP-CΔC10mut exerts a poison polypeptide effect leading to improper asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Myofilament-enriched protein fractions from frozen mouse hearts were isolated and subjected to SDS-PAGE and Western blot analysis for total and phosphorylated cMyBP-C and cardiac troponin I as described previously [10,17]. Total RNA isolation, quantitative expression of MYBPC3 and hypertrophic gene markers, and RNA-seq were performed as previously described [10,17,23].…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Myofilament-enriched protein fractions from frozen mouse hearts were isolated and subjected to SDS-PAGE and Western blot analysis for total and phosphorylated cMyBP-C and cardiac troponin I as described previously [10,17]. Total RNA isolation, quantitative expression of MYBPC3 and hypertrophic gene markers, and RNA-seq were performed as previously described [10,17,23].…”
Section: Molecular Analysesmentioning
confidence: 99%
“…These studies showed that transcripts originating from the affected allele are subject to alternative splicing mechanisms that lead to skipping of exon 33. The resulting protein has a C10 domain with 62 residues removed and 55 added, mislocalizes to the Z-disc and its overexpression is sufficient to cause HCM in transgenic mice [46,47]. However, the probability of the alternative splicing event in human and the resulting amount of mutant protein remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While many previous studies utilized C0-C2 or C1-C2 constructs [13][14][15][16][17][18][19][20], little is known about the biochemical properties of the C2 domain. Since MYBPC3 Δ25bp alone is not a penetrant factor for development of HCM and has been characterized before [45][46][47][48], this study focuses on the impact of the D389V mutation in the C2 domain of MyBPC. Residue D389 lies in a region of the C2 domain that is highly conserved across mammals (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Inherited hypertrophic cardiomyopathy (HCM) is the common type of ICM 1, 2 . The main pathological manifestation of inherited HCM is left ventricle and ventricular septal asymmetry hypertrophy, which is also the main cardiogenic cause of sudden death in this disease 2,3 . The latest epidemiological investigation shows that most hereditary modes of HCM are autosomal dominant with an incidence rate of about 200/100,000, and there is no difference in genders 4 .…”
Section: Introductionmentioning
confidence: 99%